Prognostic Significance of the Albumin to Fibrinogen Ratio in Peritoneal Dialysis Patients - Xia, Wenkai; Kuang, Meisi; Li, Chenyu; Yao, Xiajuan; Chen, Yan; Lin, Jie; Hu, Hong (Frontiers in Medicine, 2022)
Background: Albumin to fibrinogen ratio (AFR) has been demonstrated as a predictor of mortality in various diseases. The aim of this study was to evaluate the prognostic value of AFR to predict mortality in peritoneal dialysis (PD) patients Methods: We retrospectively analyzed 212 incident PD patients from January 2010 and December 2017 and follow them until December 2019. Using receiver operating curves (ROC) to determine the optimal cut-off point for AFR at baseline level to predict overall and cardiovascular mortality during the follow-up period. Kaplan-Meier curve and Cox regression analysis were applied to evaluate the association between AFR and all-cause and cardiovascular mortality. Results: The optimal threshold for AFR to predict mortality was 8.48. A low AFR was strongly correlated with worse all-cause and cardiovascular mortality in PD patients. Multivariate analysis revealed that elevated AFR was an independent marker to predict reduced all-cause and cardiovascular mortality (HR 2.41, 95%CI 1.11-5.22, P=0.026; HR 2.18, 95%CI 1.21-3.95, P=0.010, respectively). Conclusions: Patients with a high AFR level had a reduced all-cause and cardiovascular mortality. AFR may serve as a potential prognostic biomarker in PD patients.